2014
DOI: 10.1016/j.earlhumdev.2014.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Associations between maternal scaffolding and executive functioning in 3 and 4year olds born very low birth weight and normal birth weight

Abstract: Background Deficits in executive function, including measures of working memory, inhibition and cognitive flexibility, have been documented in preschoolers born very low birth weight (VLBW) compared with preschoolers born with normal birth weight (NBW). Maternal verbal scaffolding has been associated with positive outcomes for both at-risk and typically developing preschoolers. Aims The purpose of this study was to examine associations between maternal verbal scaffolding, Verbal IQ (VIQ) and executive functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 60 publications
0
27
0
3
Order By: Relevance
“…To exert impulse control, preschool children rely more on external control and structure provided by adults, than on internal executive control mechanisms [34]. Indeed, parental scaffolding that provides structure and support (e.g., reminding a child to stay seated) can enhance a young child's impulse control [35]. …”
Section: Preschool Years: Developing Efmentioning
confidence: 99%
“…To exert impulse control, preschool children rely more on external control and structure provided by adults, than on internal executive control mechanisms [34]. Indeed, parental scaffolding that provides structure and support (e.g., reminding a child to stay seated) can enhance a young child's impulse control [35]. …”
Section: Preschool Years: Developing Efmentioning
confidence: 99%
“…Among these, sensitive parenting (e.g., Towe-Goodman et al, 2014; Sulik et al, 2015) and parental scaffolding (e.g., Lowe et al, 2014) showed to be associated with EF in young children in several studies. It is assumed that parents serve as self-regulating catalysts and attention-switches for their children while their brain structures form, which will later be in charge of these mechanisms (e.g., Carlson, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…According to Carlson (), three distinct dimensions of parenting are likely to contribute to the development of EF: (1) two behavioral dimensions, namely parental scaffolding (i.e., the ability of the caregiver to offer children age‐appropriate problem‐solving strategies) and sensitivity (i.e., the ability of the caregiver to respond to the child's signals in a consistent and appropriate manner), and (2) a verbal dimension, referring to the tendency to use mental‐state terms while talking to the child. Indeed, the contributions of parental scaffolding (Bibok, Carpendale, & Müller, ; Hammond, Müller, Carpendale, Bibok, & Libermann‐Finestone, ; Landry, Miller‐Loncar, Smith, & Swank, ; Lowe et al, ) and sensitivity (Blair et al, ; Towe‐Goodman et al, ) for the development of EF skills have been the focus of recent empirical interest. However, less attention has been given to the role of parental mental‐state talk—referring to the child's, one's own and others’ desires, emotions, and cognitions—when dialoguing with the child.…”
Section: Introductionmentioning
confidence: 99%